(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This thesis explores the methods of teaching religious studies (dinshunoslik) in higher education institutions, emphasizing innovative, student-centered, and interdisciplinary approaches. It examines the role of adaptive learning technologies, Scriptural Reasoning, immersive simulations, and AI-assisted tools in enhancing student engagement, critical thinking, and interpretive skills. The study highlights the importance of integrating ethical considerations, cross-disciplinary perspectives, and practical applications into the curriculum. It also underscores the necessity of continuous professional development for instructors to ensure effective implementation of modern pedagogical strategies. The findings suggest that a combination of technological, experiential, and interdisciplinary methods can significantly improve the quality of religious studies education, fostering graduates capable of analytical reasoning, ethical reflection, and intercultural understanding.